2015
DOI: 10.12944/cwe.10.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Technical Efficiency of Shrimp Farming in Andhra Pradesh: Estimation and Implications

Abstract: Shrimp farming is a key subsector of Indian aquaculture which has seen a remarkable growth in the past decades and has a tremendous potential in future. The present studyanalyzes thetechnical efficiency of the shrimp famers of East Godavari district of Andhra Pradesh using the Stochastic Production Frontier Function with the technical inefficiency effects. The estimates mean technical efficiency of the farmers was 93.06 % which means the farmers operate at 6.94 % below the production frontier production. Age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…The intensive farming is more lucrative than that of semi‐intensive and traditional by adoption of advanced practices (Ahmed, 2007). Alike agriculture, the fertilizer, pesticides and energy consumption also influence the total harvest biomass of the shrimp in farm (Sivaraman et al., 2015). The decision regarding farms profoundly relies on socio‐economic physiognomies of the farmers including the age, education, experiences and knowledge gaining, which directly affect the technical efficiency of the shrimp farms (Van Thap et al., 2016; Tung, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intensive farming is more lucrative than that of semi‐intensive and traditional by adoption of advanced practices (Ahmed, 2007). Alike agriculture, the fertilizer, pesticides and energy consumption also influence the total harvest biomass of the shrimp in farm (Sivaraman et al., 2015). The decision regarding farms profoundly relies on socio‐economic physiognomies of the farmers including the age, education, experiences and knowledge gaining, which directly affect the technical efficiency of the shrimp farms (Van Thap et al., 2016; Tung, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The decision regarding farms profoundly relies on socio‐economic physiognomies of the farmers including the age, education, experiences and knowledge gaining, which directly affect the technical efficiency of the shrimp farms (Van Thap et al., 2016; Tung, 2010). The experiences of the farmers positively enhanced the shrimp production whereas the same for the education and occupation type (Sivaraman et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The results suggest high degrees of technical inefficiency exist among shrimp farmers. Sivaraman et al [43], on the other hand, analyzed the technical efficiency of shrimp farmers in the East Godavari district of Andhra Pradesh using SFA and found that they were 93.06% technically efficient in producing shrimp. Age, education and experience of the farmers, as well as their membership in farmers' associations and societies, significantly affected technical efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Segundo os autores, há um grande número de pequenos e médios produtores, que se caracterizam pela utilização de sistemas extensivos e semi-intensivo de produção, diferente do quadro encontrado no Ceará, caracterizado por produtores que utilizam sistemas semi-intensivo e intensivo de produção. Essas características regionais não 1 No mundo, a eficiência técnica da carcinicultura foi investigada na Malásia (Islam et al, 2014), Vietnã (Kiet & Fisher, 2014), Bangladesh (Begum et al, 2013), e Índia (Sivaraman et al, 2015). devem ser negligenciadas e, para contornar esta limitação, nesse estudo, utiliza-se a função de metafronteira de produção, a qual permite comparar o grau de eficiência técnica entre regiões, tendo como base a mesma linha de referência (benchmark).…”
Section: / 544unclassified